Heterobeltiosis and standard heterosis for seed yield and important traits in Brassica juncea - HS Meena; Bhagirath Ram; Arun Kumar; BK Singh; PD Meena; VV Singh; Dhiraj Singh (Journal of Oilseed Brassica, 2026)
Genetic study was carried out to estimate heterobeltiosis (better parent heterosis) and standard heterosis forisolation of superior cross combinations of Indian mustard [Brassica juncea (L.) Czern. & Coss.]. Thirty sixF1 crosses along with thirteen B. juncea parental genotypes planted at the Directorate of Rapeseed-MustardResearch (DRMR), Bharatpur, experimental farm during 2011-12 were evaluated for twelve characters,including seed yield / plant (g), plant height (cm), point to first branch (cm), number of primary branches, mainshoot length (cm), point to first siliqua (cm), number of siliquae on main shoot, siliqua length (cm), number ofseeds per siliqua, 1000-seed weight (g), days to maturity and percent oil content. Analysis of variancerevealed considerable genetic variability among parents and F1 crosses for all the traits. Five crosses viz.,DRMR 2486 × Ashirwad, DRMR 2243 × NRCHB 101, DRMR 2269 × NRCHB 101, DRMR 2341 ×NRCDR 2, and DRMR 2613 × NRCDR 2 possessed high heterosis and higher per se performance overbetter parent and standard check. In many crosses, highly significant heterosis was observed for point to firstbranch, number of primary branches, main shoot length, point to first siliqua and number of seeds / siliqua.The high yielding cross combinations from this study can be utilized in future breeding programmes fordevelopment of high yielding genotypes